“Aplicaciones pedagógicas del rotavapor en procesos de transformación agroindustrial” - Lanchimba Fernandez, Jefferson Rodolfo (2023)
The objective of this project was to carry out a Manual of Pedagogical Applications of the Rotavapor Equipment in Agroindustrial transformation processes, with the purpose of incorporating the use of the equipment in Research and teaching practices in the Agroindustrial Engineering Career, the same one that is in charge of extracting assets using the principles distillation method. The use and operation manual details the parts of the equipment and the function that each of them fulfills when carrying out the practice. The technical data of the equipment will be the most important values at the moment of introducing the samples for their distillation, a record of the activities that must be fulfilled before and after the practice is attached. The purpose of the maintenance manual is to know the types of maintenance that must be carried out on the Rotavapor to prevent damage, the maintenance that will be carried out on the equipment are: routine, preventive and corrective, with their respective records of the activities that must be fulfilled so as not to cause damage and prolong the useful life of the equipment. To finish the investigation, pedagogical applications were carried out in the bromatology laboratory using the equipment practices in the different extractions of fruit and vegetable pigments by the distillation method, with the obtaining of the vegetable pigments during the distillation the corresponding percentages were obtained for the spinach pigment had 2.4%, for the oregano pigment it was 3.4% and finally for the beetroot pigment a value of 3% was achieved, which is evidenced in the reports of the practices. In addition, a matrix is attached in which the different subjects are detailed, where the equipment is used for the respective practices or investigations.